Beware of Mr. Baker [videorecording (DVD)] - Bulger, Jay; Bulger, Jay; Bulger, Jay; Baker, Ginger; Clapton, Eric; Lydon, John, 1956-; Bruce, Jack; Watts, Charlie; Hart, Mickey; Ramone, Marky; Santana, Carlos (Viva Pictures, 2013)
The documentary about the ailing-yet-ferocious Ginger Baker, the brilliant and wildly self-destructive drummer for Cream and Blind Faith. An almost impossible man to be around, he allows the director unprecedented access--even if he strikes him violently on the nose with his cane on the final day of filming.